(untitled) (Research, Society and Development, 2022)
Descriptive, cross-sectional, survey-type research, aimed to analyze how nursing students from a public university refer to their skills in Hand Hygiene and Infection Control achieved in the classroom and in practical situations. Data were collected between July and October 2020 using the Brazilian version of the “Health Professional Education in Patient Safety Survey” questionnaire, with analyses carried out using frequencies, means and standard deviations for each score. Normality was analyzed by the Kolmogorov-Smirnoff test and the t test to compare the means. Of the invited students, 69 (28.39%) participated, being 20 (33.9%) of the senior year of Nursing School and 49 (26.6%) of the newly registered nurses. Self-reported Hand Hygiene competence scored was 100% and 95% and Infection Control was 90% and 65% by seniors students (n=20), respectively learned in classroom setting versus the clinical setting, significantly lower in Infection Control (p = 0.0357). Of the newly registered nurses (n=49) self-reported competence in Hand Hygiene was 97.96% and 100% and in Infection Control was 85.71% and 89.80%, both related to learning in classroom setting versus the clinical setting, respectively. The learning comparison between senior students and newly registered nurses was significantly different (p = 0.0084) only in Infection Control clinical setting. It’s necessary to enhance the learning in classroom setting and clinical setting not only in Hand Hygiene, but in Infection Control.